Strategi Penguatan Kapasitas Badan Usaha Milik Desa (BUMDes) Berbasis Digital - Haeruddin; Ibrahim Ahmad; Aigistina, Aigistina (ADPERTISI, 2025)
This community service activity aims to strengthen the institutional capacity of Village-Owned Enterprises (BUMDes) through a contextual and sustainable digital approach. Conducted in Sampulungan Village, Takalar Regency, the program employed an educational and participatory approach, encompassing training sessions, outreach activities, and simulations on the use of digital tools such as Google Sheets, Google Forms, and QR Codes. The results indicate that the majority of participants experienced an increased understanding of the importance of digitalization in village enterprise governance and demonstrated readiness to adopt technology-based systems for record-keeping and promotion. Group discussions and evaluations revealed that the main challenges were limited digital literacy, infrastructure constraints, and organizational culture. Accordingly, strategic recommendations include continuous mentoring, engagement of village youth as digitalization agents, and replication of the program in other villages. This initiative reinforces the role of higher education institutions in community empowerment and demonstrates that digital transformation at the village level is achievable through cross-sector collaborative approaches.